PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEB PADA MATA PELAJARAN SEJARAH DI KELAS X MPLB SMK KANISIUS UNGARAN - Khoirur Rozikin; Buitas Ribka Letkamang; Candra Supriadi; Nuris Dwi Setiawan; Unang Achlison (STEKOM PRESS, 2024)
One effective way in the world of education, especially in teaching and learning activities, is to keep up with current developments by utilizing existing technology. At Kanisius Ungaran Vocational School in Class X MPLB there is no web-based interactive learning media for the History subject. In this regard, there is a need to develop web-based interactive learning media so that teaching and learning activities are more interesting and enjoyable, especially in the subject of History. The benefit of this research is that it can apply the knowledge possessed by researchers in developing web-based interactive learning media in the History subject in class X MPLB Kanisius Vocational School Ungaran. Apart from that, this research is also expected to increase learning creativity and innovation, as for the practical benefits of this research, it can make it easier for teachers and students in teaching and learning activities in the subject of History